2019
DOI: 10.1089/jwh.2019.7849
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Centers for Disease Control and Prevention's Case Investigation of Cervical Cancer Study

Abstract: Background: Despite advances in cervical cancer screening, a significant number of women in the United States have not received adequate screening. Studies have suggested that approximately half of the women who developed cervical cancer were not adequately screened. The Centers for Disease Control and Prevention (CDC) Case Investigation of Cervical Cancer (CICC) Study took a unique approach to reconstruct the time before a woman's cervical cancer diagnosis and understand the facilitators and barriers to scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Details of the study are reported elsewhere. 4 Study packets were mailed containing questionnaires and requests for consent to collect data from medical records. Of the 1,730 eligible women, 28% (n = 481) enrolled in the study and 23% (n = 400) consented to chart abstraction.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of the study are reported elsewhere. 4 Study packets were mailed containing questionnaires and requests for consent to collect data from medical records. Of the 1,730 eligible women, 28% (n = 481) enrolled in the study and 23% (n = 400) consented to chart abstraction.…”
Section: Methodsmentioning
confidence: 99%
“…Additional information on response rate has been reported. 4 Of the women who consented, charts were available for 376 (94%). Abstractors were asked to evaluate the completeness of the data they were able to obtain for each woman based on requests made and the responses.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations